2021
DOI: 10.3346/jkms.2021.36.e38
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Linkage of COVID-19 Outbreaks at Two University-affiliated Hospitals in the Seoul Metropolitan Area in March 2020

Abstract: Background: Coronavirus disease 2019 (COVID-19) outbreaks emerged at two universityaffiliated hospitals in Seoul (hospital A) and Uijeongbu City (hospital S) in the metropolitan Seoul area in March 2020. The aim of this study was to investigate epidemiological links between the outbreaks using whole genome sequencing (WGS) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: Fifteen patients were enrolled in the study, including four non-outbreak (A1-A4) and three outbreak cases (A5-A7) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Policy change was also called for in a Boston hospital study: virus genomes with shared substitutions suggested at least two patient-to-staff transmission events, despite an apparent lack of aerosol-generating procedures and the staff wearing masks and face shields 44 . In South Korea, the observation of eight near-identical B.2.1 lineage genomes across two Seoul hospitals suggested that the outbreak in one hospital was seeded by a patient transferred from the other 45 . Multiple introductions were inferred for an outbreak at a San Francisco nursing facility, with one worker, who had also worked in Washington State, implicated in the introduction of WA1-related virus genomes 46 .…”
Section: Outbreak Phylogeneticsmentioning
confidence: 99%
“…Policy change was also called for in a Boston hospital study: virus genomes with shared substitutions suggested at least two patient-to-staff transmission events, despite an apparent lack of aerosol-generating procedures and the staff wearing masks and face shields 44 . In South Korea, the observation of eight near-identical B.2.1 lineage genomes across two Seoul hospitals suggested that the outbreak in one hospital was seeded by a patient transferred from the other 45 . Multiple introductions were inferred for an outbreak at a San Francisco nursing facility, with one worker, who had also worked in Washington State, implicated in the introduction of WA1-related virus genomes 46 .…”
Section: Outbreak Phylogeneticsmentioning
confidence: 99%
“…In addition to the risk of community transmission, caregivers also showed a remarkably high attack rate compared to other occupations ( Table 4 ). The caregiver management issue was not only a problem in Korea during the COVID-19 outbreak [ 14 - 16 ], but also during the Middle East respiratory syndrome outbreak in May 2015, in which 40% of confirmed cases were in family members of patients or caregivers [ 17 , 18 ]. Since caregivers are not licensed medical practitioners, they do not have adequate knowledge regarding infection control and personal hygiene practices, and they perform various actions with patients owing to the lack of medical personnel [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early in the pandemic (March 2020), the incidence of patients with COVID-19 exceeded the availability of single isolation rooms in many UK hospitals [3]. Studies exploring these HAI COVID cases have focused on the role of the healthcare worker (HCW) [4,5], but in some situations, the source of the infection has been linked back to the patients' family members and/or privately hired carers [6,7]. Previously the role of family carers in the clinical setting was linked to the spread of Middle East Respiratory Syndrome (MERS) during an outbreak in 2015 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously the role of family carers in the clinical setting was linked to the spread of Middle East Respiratory Syndrome (MERS) during an outbreak in 2015 [7][8][9][10]. A recent COVID-19 outbreak report noted the role of multiple occupancy room settings, where patients' caregivers stay next to the patient, as potentially facilitating the spread of the virus [6,7,9]. Despite these studies and others [11][12][13] acknowledging the role of family carers in the transmission of infections during outbreaks, little attention has been given to this issue.…”
Section: Introductionmentioning
confidence: 99%